Tafsir Tarbawi Concept as Inspiration in the Islamic Education Curriculum - M. Riad; Iskandar Mirza (Penerbit Hellow Pustaka, 2025)
Education is the foundation of a strong nation. The curriculum determines learning success and prepares students for the future. Educational planning must be based on devotion to Allah. The curriculum is a number of subjects taken by students at an educational institution, and in a broad sense the curriculum is “what persons experience in a setting” all learning experiences and cultures created by an educational institution to build independence and achieve the desired educational goals. Meanwhile, the Islamic education curriculum is an educational curriculum that has a foundation based on Islam, namely the Koran and Hadith, who really pays attention to the condition of human personality or students such as physical aspects, intellectual aspects and spiritual aspects. The Al-Qur'an as the first source of law is the foundation for preparing the Islamic education curriculum. However, it is difficult for us to find special words in the Koran such as manhaj al-dirasah as words that indicate the curriculum. So the curriculum in Tafsir Tarbawi studies is in the form of the expanse of values, culture, character, principles and teachings that lie in the Qur’an.